2002
DOI: 10.1104/pp.002014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Diadinoxanthin Pool Size on Photoprotection in the Marine Planktonic Diatom Phaeodactylum tricornutum  

Abstract: The pool size of the xanthophyll cycle pigment diadinoxanthin (DD) in the diatom Phaeodactylum tricornutum depends on illumination conditions during culture. Intermittent light caused a doubling of the DD pool without significant change in other pigment contents and photosynthetic parameters, including the photosystem II (PSII) antenna size. On exposure to high-light intensity, extensive de-epoxidation of DD to diatoxanthin (DT) rapidly caused a very strong quenching of the maximum chlorophyll fluorescence yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
270
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(301 citation statements)
references
References 42 publications
18
270
3
1
Order By: Relevance
“…These experiments indicated that PSII electron transport might over-estimate the primary production under some conditions, because oxygen evolution rates were found to be lower than PSII electron flow (Gilbert et al 2000). Several explanations for this disparity have been suggested: (a) Cyclic electron flow around PSII (Prasil et al 1996;Lavaud et al 2002) (b) Water-water cycle (Asada 1999) where oxygen uptake on the acceptor side of PSI leads to superoxide which is then dismutated to H 2 O 2 and then detoxified to water and (c) Cyclic electron flow around PSI (Bendall and Manesse 1996) These processes can be summarised as alternative electron cycling (AEC) which are not energetic losses (such as non-photochemical quenching: NPQ), because at least the water-water cycle and the cyclic flow around PSI generate a proton gradient which can be used for additional ATP synthesis. Therefore, it is suggested that alternative electron cycling is a normal stress response and might be of less importance under balanced growth conditions.…”
Section: Alternative Electron Cycling (Aec)mentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments indicated that PSII electron transport might over-estimate the primary production under some conditions, because oxygen evolution rates were found to be lower than PSII electron flow (Gilbert et al 2000). Several explanations for this disparity have been suggested: (a) Cyclic electron flow around PSII (Prasil et al 1996;Lavaud et al 2002) (b) Water-water cycle (Asada 1999) where oxygen uptake on the acceptor side of PSI leads to superoxide which is then dismutated to H 2 O 2 and then detoxified to water and (c) Cyclic electron flow around PSI (Bendall and Manesse 1996) These processes can be summarised as alternative electron cycling (AEC) which are not energetic losses (such as non-photochemical quenching: NPQ), because at least the water-water cycle and the cyclic flow around PSI generate a proton gradient which can be used for additional ATP synthesis. Therefore, it is suggested that alternative electron cycling is a normal stress response and might be of less importance under balanced growth conditions.…”
Section: Alternative Electron Cycling (Aec)mentioning
confidence: 99%
“…3a). For that reason, it is calculated as (F m -F¢ m )/F¢ m (or F o -F¢ o /F¢ o ; Lavaud et al 2002). In higher plants, green algae and dinoflagellates, where the NPQ mechanism has been investigated, it consists of three components ( Fig.…”
Section: Effect Of Light Stress On Fluorescence Signatures and Theirmentioning
confidence: 99%
“…On the other hand, a wide variability of the capacity for nonphotochemical quenching is commonly seen in photosynthetic organisms. When calculated according to Bilger and Björkman This value increases to 0.5 in cyanobacteria (22) and up to 12 in diatoms (23). In addition, it appears that not only the amplitude but also the nature of the NPQ response can vary between organisms, even within the two model organisms mentioned above.…”
mentioning
confidence: 95%
“…For example, they show an outstanding capacity to cope with light stress. Their ability to dissipate excess energy in high light can surpass that of plants, as witnessed by the impressive levels of nonphotochemical quenching (NPQ) of chlorophyll fluorescence observed in the model diatom Phaeodactylum tricornutum in some conditions (7). The term NPQ describes the enhancement of thermal dissipation of absorbed energy that occurs in the pigment-containing proteins of photosystem (PS) II, whenever light absorption exceeds the maximum rate of CO 2 assimilation.…”
mentioning
confidence: 99%